Studies in Arthur Schnitzler (The University of North Carolina Press, 2021)
This valuable collection of eight original and penetrating essays by American scholars honors the centenary of the Austrian dramatist's birth. The contributors are Kurt Bergel, Joseph Dayag, Lore Foltin, Robert Kann, Richard Lawson, Walter Perl, Herbert Reichert, and Robert Donald Spector and they attend to themes from depictions of death to the influence of Nietzsche on Schnitzler's work and his reception in France.